A rare cause of cyanosis and hypoxia that should not be forgotten after implantable cardioverter defibrillator implantation - Uğur Canpolat; Nihan Bahadır; Levent Şahiner; Kudret Aytemir (KARE Publishing, 2017)
Transvenous pacemaker or implantable cardioverter defibrillator (ICD) implantation procedures are usually performed under local anesthetic, and prilocaine is the most common agent to be used. The data regarding methemoglobinemia after cardiac device implantation are scarce. Thus, presently described is the case of a 47-year-old female patient with arrhythmogenic right ventricular cardiomyopathy/dysplasia who underwent ICD implantation for secondary prophylaxis and developed cyanosis as a result of prilocaine-associated methemoglobinemia. Prilocaine was administered during the procedure. To our knowledge, this is the second case in the literature presenting methemoglobinemia due to local anesthetic after transvenous cardiac device implantation.